ヒガシ ナンキョク オメガ ミサキ ノ チガクテキ カンサツ - 森脇, 喜一; モリワキ, キイチ; MORIWAKI, Kiichi (1980)
P(論文) 第18次南極地域観測隊オメガ岬調査に参加し,次の観察を行った.オメガ岬は,昭和基地付近の他の露岩と同様,氷河作用を受けたいくつかの特徴を有する.過去の氷床はオメガ岬全域を覆っていた.擦痕は異なる方向の2群に分けることができ,これから,過去の氷の流動は,よリ古いSE-NW方向からより新しいESE-WNW方向へ変化したこと,露岩域の風化程度などから,氷からの解放は北部がかなり早く,氷の後退はゆっくりと行われたことが知られる.ただし,露岩上へのモレーン堤の形成はみられない.露岩背後のモレーン堤は,昭和基地付近では最大級であるが,厚くなく,剪断モレーンである.モレーン堤や露岩上の京成堆積物には構造土の発達が顕著である.構造土での地温測定の結果,最低温度も氷点下には下がらなかったが,この時期がたまたま異常高温であったためと考えられる.大陸氷縁辺部での融氷水流も顕著で,流量測定の結果,水流1本で6×10^3t/day以上の値が得られた. The reconnaissance geomorphological survey of Cape Omega was made by the author in January 1977. Cape Omega has glaciated features same as other ice-free areas in the vicinity of Syowa Station. The past ice sheet had covered Cape Omega completely. Abundant glacial striae are preserved on the bedrock, and they are classified into two grouos, i. e. SE-NW trending ones and ESE-WNW trending ones. The former group indicates the older direction of ice flow, and the latter indicates the younger. Judging from the degree of weathering of the bedrock, the northern part of Cape Omega was freed from the ice sheet earlier than the southern part. The moraine in the marginal part of the ice sheet close to the rocks is the biggest one among those in the vicinity of Syowa Station. Patterned ground develops well on the moraine bank and on the glacial deposits on the rocks. Measurement of earth temperature in the sorted polygon was made for 2 days. Measured minimum temperature did not fall below freezing point. It may be ascribed to some extent to the fact that the period of measuring was abnormally high temperature period near Syowa Station. In the summer season, meltwater streams occur in the marginal zone of the ice sheet. Several meltwater streams develop in a zone of 2.5 km in width in the Cape Omega area. Measurement of flow rate was made at one of those, and the amount of now of the meltwater stream was calculated to be over 6×10^3t/day. departmental bulletin paper